Faktor-faktor yang Mempengaruhi Penerimaan Pajak Pulau Jawa - Suganda, Tri Rizki Handayani; Aminda, Renea Shinta (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
This study is a quantitative study aimed at assessing the effect of population, per capita income, inflation and the number of motorized vehicles on tax revenues in all provinces in Java. The sample used in this study used a saturated sampling technique in six provinces in the 2015-2020 period, thus the total sample used was 36 data sourced from the Central Statistics Agency and the Regional Revenue Agency. Testing the hypothesis in this study using panel data analysis with the Eviews 10 program. Where the results of the study show that population, per capita income and inflation have an influence on tax revenue, while the number of motorized vehicles has no effect on tax revenue.